Presynaptic and Postsynaptic Mechanisms of a Novel Form of Homosynaptic Potentiation at Aplysia Sensory-Motor Neuron Synapses - Jin, Iksung (J Neurosci, 2003)
Previous studies have shown that homosynaptic potentiation produced by rather mild tetanic stimulation (20 Hz, 2 sec) at Aplysia sensory-motor neuron synapses in isolated cell culture involves both presynaptic and postsynaptic Ca(2)(+) (Bao et al., 1997). We have now investigated the sources of Ca(2)(+) and some of its downstream targets. Although the potentiation lasts >30 min, it does not require Ca(2)(+) influx through either NMDA receptor channels or L-type Ca(2)(+) channels. Rather, the potentiation involves metabotropic receptors and intracellular Ca(2)(+) release from both postsynaptic IP(3)-sensitive and presynaptic ryanodine-sensitive stores. In addition, it involves protein kinases, including both presynaptic and postsynaptic CamKII and probably MAP kinase. Finally, it does not require transsynaptic signaling by nitric oxide but it may involve AMPA receptor insertion. The potentiation, thus, shares components of the mechanisms of post-tetanic potentiation, NMDA- and mGluR-dependent long-term potentiation, and even long-term depression, but is not identical to any of them. These results are consistent with the more general idea that there is a molecular alphabet of basic components that can be combined in various ways to create novel as well as known types of plasticity.